2019
DOI: 10.1002/jnr.24493
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype onset in Huntington’s disease knock‐in mice is correlated with the incomplete splicing of the mutant huntingtin gene

Abstract: Huntington’s disease (HD) is a progressive neurodegenerative disorder caused by an expanded CAG repeat within the huntingtin (HTT) gene. The Q140 and HdhQ150 knock-in HD mouse models were generated such that HdhQ150 mice have an expanded CAG repeat inserted into the mouse Htt gene, whereas in the Q140s, mouse exon 1 Htt was replaced with a mutated version of human exon 1. By standardizing mouse strain background, breeding to homozygosity and employing sensitive behavioral tests, we demonstrate that the onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Exon 1 HTT fragment was found to be generated by aberrant exon 1-intron 1 RNA, which was observed only in the HD brains in which a large CAG repeat is present 20,24 . Using RT-PCR of WT and KI mouse, we confirmed the selective expression of aberrant exon 1-intron 1 RNA in the KI mouse striatum when compared with WT mouse striatum ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Exon 1 HTT fragment was found to be generated by aberrant exon 1-intron 1 RNA, which was observed only in the HD brains in which a large CAG repeat is present 20,24 . Using RT-PCR of WT and KI mouse, we confirmed the selective expression of aberrant exon 1-intron 1 RNA in the KI mouse striatum when compared with WT mouse striatum ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To dissect why D1R- and D2R-MSNs are differentially affected by HD, Lee et al (2020) highlighted thousands dysregulated protein-coding genes implicated in OXPHOS, synaptic functioning and circadian entrainment by using translating ribosome affinity purification and snRNA-seq of D1R and D2R neurons of HD patients and mouse models (R6/2 and zQ175DN, a knock-in zQ175 line without neomycin cassette) ( Franich et al, 2019 ). Strikingly, downregulation of OXPHOS and upregulation of neurotrophin pathway genes in D2R neurons indicated a cell-type specific response to the disease ( Figure 1D ).…”
Section: Do D1r- and D2r-msns Differentially Respond To The Hd Mutatimentioning
confidence: 99%
“…The HTT gene contains 67 exons, and we have previously shown that exon 1 does not always splice to exon 2 resulting in the production of a small transcript ( Httexon1 ) that terminates at cryptic polyadenylation sites within intron 1. This occurs in knock-in mouse models ( Sathasivam et al , 2013 ; Franich et al , 2019 ), where the level of incomplete splicing correlates with the appearance of disease phenotypes, and in Huntington’s disease post-mortem brains and cell lines ( Neueder et al , 2017 ). The Httexon1 transcript contains a stop codon at the beginning of intron 1 and is translated to produce the highly pathogenic exon 1 HTT protein ( Sathasivam et al , 2013 ; Neueder et al , 2018 ), by the same mechanism as occurs in R6/2 mice ( Mangiarini et al , 1996 ).…”
Section: Introductionmentioning
confidence: 99%